Associated factors with the development of multidrug resistant pulmonary tuberculosis in the department of Piura, Peru 2009-2014 - Susy Bazan-Ruiz (Asociación Colombiana de Infectología, 2019)
Objetive: To know the associated socio-economic factors for the development of multidrug-resistant (MR) pulmonary tuberculosis (PT) in Piurana population during the years 2009-2014. Materials and methods: Observational study in patients with PT MR and non MR. Data from the records of the Tuberculosis Prevention and Control Strategy of the Regional Health Department of the department of Piura were taken. A statistical analysis of association and its confidence intervals was performed, with the use of generalized linear models statistics and their confidence intervals, with the use of generalized linear models. Results: Factors that had an association with PT MR were diagnosed as treatment failure at admission, having a contact with a MR/XDR PT patient, who had an irregular treatment, being classified as a proven failure, having a history of treatment and that this treatment was with several drugs. In the multivariate analysis, the only one who maintained the association was the antecedent of being a multi-treated patient, had an PR = 4.47 (95% CI: 1.28-15.63). Conclusions: Being multi-treated showed a great association with the greater frequency of PT MR, so it can be taken into account as a baseline study, developed in a city in northern Peru and that shares characteristics with other cities and other countries with similar realities